2022
DOI: 10.3390/nu14112266
|View full text |Cite
|
Sign up to set email alerts
|

Review of Kangaroo Mother Care in the Middle East

Abstract: Mothers and newborns have a natural physiological requirement to be together immediately after birth. A newborn has a keen sense of smell and will instinctively seek out the mother’s nipple and begin breastfeeding if placed skin-to-skin with her. This practice is known as Kangaroo Mother Care (KMC). It was first suggested in 1978 and has been recommended by the World Health Organization (WHO) as a means to ensure successful breastfeeding. It is well documented that KMC is associated with positive breastfeeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many studies have documented data on attitude, knowledge and implementation of KMC among nurses in Saudi Arabia. [33][34][35] In the study region, it was found that KMC was less often in practice due to newborn infants often being separated from their mothers and hence delayed breastfeeding initiation for hours or days was observed. 17 The present study's aim was to determine the hormonal levels after intermittent KMC practice in mothers who had emergency C-section and compare them with the non-KMC C-section group.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have documented data on attitude, knowledge and implementation of KMC among nurses in Saudi Arabia. [33][34][35] In the study region, it was found that KMC was less often in practice due to newborn infants often being separated from their mothers and hence delayed breastfeeding initiation for hours or days was observed. 17 The present study's aim was to determine the hormonal levels after intermittent KMC practice in mothers who had emergency C-section and compare them with the non-KMC C-section group.…”
Section: Discussionmentioning
confidence: 95%
“…The lack of coordination among different professionals is often considered the main obstacle [ 25 ]. Moreover, there is a need for additional and ongoing research to describe KC in various countries, especially in the Middle East [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research are similar to those of previous research on the same topic. Patient care activities with time-sensitive and core tasks need to receive higher priority than needs that may be perceived as time-consuming and not urgent in terms of patient safety, such as comfort care and parental emotional support, and thus there may be a perception that missing them will not have serious impacts on patients’ health [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Breastfeeding is the recommended feeding method by the World Health Organization for the first six months of life. 4 Breast milk is an important source of intestinal microbiota for infants. 5 and breastfeeding enables the vertical transmission of microorganisms from mother to infants.…”
Section: Introductionmentioning
confidence: 99%